2020
DOI: 10.1055/s-0040-1715575
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ceroid Lipofuscinosis: Clinical and Laboratory Profile in Children from Tertiary Care Centre in South India

Abstract: Neuronal ceroid Lipofuscinosis (NCL), inherited disorders of lysosomal storage disorders, constitute the most common progressive encephalopathies with an incidence of 1.3 to 7 in 100,000 live births. We report clinical, electrophysiological, radiological, ultrastructural, and molecular genetic features of NCL. This is a retrospective review, in a tertiary care center from January 2016 to December 2019. All children with clinical features of NCL and confirmed by pathogenic mutation and/or enzyme assay were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Thus, a multimode approach played a role in the diagnosis of NCL." 1 We agree that observations in the present report might be clinically useful. Some clinical features might be more common in CLN1, whereas others are more common in CLN2.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, a multimode approach played a role in the diagnosis of NCL." 1 We agree that observations in the present report might be clinically useful. Some clinical features might be more common in CLN1, whereas others are more common in CLN2.…”
supporting
confidence: 92%
“…We would like to share ideas on “Neuronal Ceroid Lipofuscinosis: Clinical and Laboratory Profile in Children from Tertiary Care Centre in South India.” 1 Prajapati et al noted that “Infantile onset with thalamic atrophy on MRI is common in CLN1 and refractory epilepsy, visual impairment, and specific EEG changes are common … diagnosis and genetic testing in subtyping. Thus, a multimode approach played a role in the diagnosis of NCL.” 1 We agree that observations in the present report might be clinically useful. Some clinical features might be more common in CLN1, whereas others are more common in CLN2.…”
mentioning
confidence: 99%
“…Pathogenic mutations in CLN genes ( CLN1 , CLN2 , CLN3 , CLN5 , CLN6 , CLN7 , CLN8 , CLN10 , CLN13 , CLN14 , and CLCN2 ) represent the principle contribution among the investigated mutations, and affected patients were of age ranged from 2 to 11 years old. The main clinical features assigned to them were developmental regression, epilepsy, speech impairment, cognitive decline, vision loss, hypotonia, myoclonus, seizures, and ataxia, and their MRI scan showed cerebellar-cerebral atrophy [ 21 ]. Five novel homozygous missense mutations were reported in different genes of 5 unrelated patients; one of them c.600 G > A (p.Trp200Ser) was detected in CLN7 gene using the Sanger sequencing technique only, and the other 4 mutations c.872A > G (p.Gln 291 Arg), c.886G > C (p.Asp296His), c.446G > A (p.Gly149Asp), and (c.906 + 2 T > A) were described in genes CLN1 , CLN7 , CLN14 , and donor splice region of intron 11 of CLN3 gene, respectively, using WES.…”
Section: Discussionmentioning
confidence: 99%
“…
We thank readers for critically evaluating our research study. 1 The queries raised are addressed below.We agree with reviewers' comments on clinical features that might not be able to discriminate and might not be helpful in selecting enzyme assay for CLN1 versus CLN2. Kamate et al reported that thalamic hypointensity is common in CLN1 similar to our cohort.
…”
mentioning
confidence: 99%
“…We thank readers for critically evaluating our research study. 1 The queries raised are addressed below.…”
mentioning
confidence: 99%